2003
DOI: 10.1200/jco.2003.04.121
|View full text |Cite
|
Sign up to set email alerts
|

Minichromosome Maintenance Protein 2 Is a Strong Independent Prognostic Marker in Breast Cancer

Abstract: Mcm-2 may be of utility as a prognostic marker to refine the prediction of outcome in breast cancer, for example when combined with parameters currently used in the NPI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
126
2
6

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 138 publications
(146 citation statements)
references
References 40 publications
12
126
2
6
Order By: Relevance
“…Moreover, Mcm2-7 expression levels are powerful prognostic indicators in diverse tumour types, including cancers of the lung, breast, kidney, bladder, prostate and ovary [71][72][73][74][75][76][77]. This finding is consistent with large-scale meta-analysis of cancer microarray data, which identified up-regulation of the MCM2-6 genes as a component of poor prognostic signatures [78].…”
Section: Dna Replication Licensing and Cancersupporting
confidence: 71%
“…Moreover, Mcm2-7 expression levels are powerful prognostic indicators in diverse tumour types, including cancers of the lung, breast, kidney, bladder, prostate and ovary [71][72][73][74][75][76][77]. This finding is consistent with large-scale meta-analysis of cancer microarray data, which identified up-regulation of the MCM2-6 genes as a component of poor prognostic signatures [78].…”
Section: Dna Replication Licensing and Cancersupporting
confidence: 71%
“…RLFs, which form the core of the initiation machinery, act as relay stations coupling growth regulatory and DNA damage response pathways to chromosomal replication. We and others have demonstrated that dysregulation of the replication Ki67 Geminin P C 3 -P a r e n t a l P C 3 -e m p t y v e c t o r P C 3 -E R K 5 P C 3 -P a r e n t a l P C 3 -e m p t y v e c t o r initiation machinery is an early event in tumourigenesis and that the Mcm2-7 RLFs are powerful diagnostic and prognostic markers in a wide range of tumour types (Williams et al, 1998Stoeber et al, 1999;Wharton et al, 2001Wharton et al, , 2004Davies et al, 2002;Going et al, 2002;Stoeber et al, 2002;Gonzalez et al, 2003;Kruger et al, 2003;Padmanabhan et al, 2004;Dudderidge et al, 2005;Korkolopoulou et al, 2005;Shetty et al, 2005). Recent reports have shown that the MEK5/ERK5 pathway is implicated in the regulation of cell proliferation, and that increased MEK5/ERK5 signalling results in increased cell proliferation, invasion and metastatic spread during prostate carcinogenesis Mehta et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The constituents of the pre-RC can be regarded as relay stations coupling growth regulatory pathways with DNA replication . We and others have demonstrated in a range of different tumour types that dysregulation of the MCM proteins is an early event in tumourigenesis and have exploited these biomarkers in primary diagnosis, tumour surveillance and prognosis (Williams et al, 1998Stoeber et al, 1999Stoeber et al, , 2002Wharton et al, 2001Wharton et al, , 2004Davies et al, 2002;Going et al, 2002;Gonzalez et al, 2003;Kruger et al, 2003;Padmanabhan et al, 2004;Dudderidge et al, 2005;Korkolopoulou et al, 2005;Shetty et al, 2005). These studies have established that the superior sensitivity of MCM proteins over the standard proliferation marker Ki67 resides in the fact that these biomarkers identify not only cycling cells but also non-cycling cells with proliferative potential ).…”
mentioning
confidence: 99%
“…This novel approach thus allows a detailed assessment of tumour cell cycle kinetics that can be routinely applied to archival specimens. We and others have already demonstrated that the MCM replication-licensing factors can be exploited as prognostic markers in cancer diagnosis (Meng et al, 2001;Ramnath et al, 2001;Wharton et al, 2001;Gonzalez et al, 2003;Kruger et al, 2003). Analysis of a range of different tumour types including glial tumours is now in progress to determine whether the Geminin origin-licensing repressor and/or the Geminin/Ki67 ratio can be exploited as independent predictors of disease-free survival.…”
Section: Discussionmentioning
confidence: 99%